Antibacterial Potentials of some Toothpaste Products against some Oral Bacterial Isolates - Oluboyo, Bernard Oluwapelumi; Charles, Maihankali J; Akele, Richard; Akinseye, Funmilayo; Oluboyo, Adeola (Brazilian Dental Science, 2021)
Objetive: Manufacturers of toothpastes claim that their products are active against oral microbiome capable of causing tooth decay. The objective of this study was to investigate the manufacturers’ claim using some of the toothpaste products sold in Ado-Ekiti, Nigeria. Material and methods: The antibacterial potentials of five commercialized toothpaste products (designated sodium fluoride-zinc sulphate, benzyl alcohol-sodium fluorophosphate, sodium fluoride-eugenol, sodium fluoridesodium laurylsulfate and sodium fluoridepotassium nitrate) were tested against six oral isolates of dental caries and periodontal origin – Staphylococcus aureus, Streptococcus mitis, Streptococcus salivarius, Streptococcus pyogenes and Pseudomonas aeruginosa. The antimicrobial potentials were evaluated using modified agar well diffusion method. Various dilutions of the toothpaste products from 1:1 to 1:16 were tested against each test microorganism. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the toothpastes were determined. Results: sodium fluoride-zinc sulphate, benzyl alcoholsodium fluorophosphate and sodium fluorideeugenol toothpastes showed inhibitory effects on S. aureus, S. mitis and S. salivarius. Sodium fluoride-sodium laurylsulfate and sodium fluoride-potassium nitrate toothpastes showed no inhibitory effect on the organisms except S. pyogenes. Only sodium fluoride-potassium nitrate toothpaste inhibited E. coli while none of the toothpastes inhibited P. aeruginosa. The MIC and MBC of sodium fluoride-zinc sulphate, benzyl alcohol-sodium fluorophosphate, and sodium fluoride-eugenol toothpastes showed bacteriostatic and bactericidal effects on the organisms. Sodium fluoride-zinc sulphate, benzyl alcohol-sodium fluorophosphate, and sodium fluoride-eugenol toothpastes showed comparable effects on S. aureus, S. mitis and S. salivarius. Sodium fluoride-eugenol toothpaste was strongest against S. mitis, benzyl alcoholsodium fluorophosphates toothpaste was strongest against S. pyogenes, sodium fluoridezinc sulphate toothpaste was strongest against S. salivarius and only sodium fluoride-potassium nitrate toothpaste inhibited E. coli. Conclusion: The manufacturer’s claim is upheld by this study for sodium fluoride-zinc sulphate, benzyl alcohol-sodium fluorophosphate and sodium fluoride-eugenol toothpastes. However, sodium fluoride-sodium laurylsulfate and sodium fluoride-potassium nitrate toothpastes showed limited inhibitory potentials. Keywords Antibacterial; Caries; Oral isolates; Periodontitis; Toothpastes.